Exploring the economic significance of the surf tourism market by experience level. (March 2018) - Hritz, Nancy; Franzidis, Alexia F.
Abstract: Although it has increased in popularity, surfing as a form of active sport tourism has received little attention in relation to its economic impact. The purpose of this paper is to explore the economic significance of the surf tourism market and examine any differences in spending based on surfer experience level. A longitudinal survey yielded 706 completed surveys for analysis. Descriptive and ANOVA statistics revealed that, as a niche tourism group, surfers bring economic benefits to a destination and that there are differences between surfers based on the number of years spent surfing. Surfers typically travel in groups of two to four people and were most likely to be repeat visitors to the destination. In addition, this group spends money on a year-round basis. As surfers gain experience in their sport they are also more likely to travel more frequently and spend more money per day. Highlights: The surf tourist, as a niche market segment, can make a strong economic contribution to destinations. Surfers travel in groups, are likely to be repeat visitors, and spend money year-round at destinations. More years of surfing experience results in more frequent trips to a destination and greater daily spending. The surf tourists uses family and friends as the main source of information for planning their trips.